Implementation of Occupational Health and Safety Management System (K3) in Improving Occupational Safety at PT. Multi Jaya Samudera Belawan - Dion Riski Naibaho; Eka Fransiska; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
To avoid the risk of accidents and improve work safety in the work environment, every transport company must comply with applicable regulations in accordance with the regulations of related agencies or authorized entities. The purpose of this study is to determine the extent to which the management system (K3) has been implemented in the company PT. Multi Jaya Samudera Belawan. Thus the company hopes that the risk of work accidents in the company can be prevented so as not to cause losses or accidents. In analyzing and explaining the application of Occupational Safety and Health Management System (SMK3) in improving work safety at PT Multi Jaya Samudera Belawan, the method used in this study is field research and library research. The results of the study that the application of the Health Management System, Occupational Safety (K3) in improving occupational safety at PT. Multi Jaya Samudera Belawan has not been running optimally which is marked by the existence of several staff in this company who do not use PPE in carrying out their work. PT. Multi Jaya Samudera only declared K3 commitment orally, so that the K3 organization in writing has not been formed. For this reason, a written commitment is needed in the application of K3 at PT. Multi Jaya Samudera Belawan to immediately form a responsible K3 organization and its function can be carried out well to reduce disease and work accidents, so that it is expected to be a reference for work safety management systems.